2018
DOI: 10.1136/bmjopen-2017-017477
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tobacco use and perceptions of student health professionals about cessation training: results from Global Health Professions Students Survey

Abstract: IntroductionHealth professionals play an important role in providing advice to their patients about tobacco prevention and cessation. Health professionals who use tobacco may be deterred from providing cessation advice and counselling to their patients. We aimed to provide prevalence estimates of tobacco use among student health professionals and describe their attitudes towards tobacco cessation training.MethodsCountry-wise aggregate data from the Global Health Professions Student Survey on ‘current cigarette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 52 publications
(43 reference statements)
4
30
0
6
Order By: Relevance
“…10 Countrywide aggregate data from the GHPSS published in 2018 found the highest prevalence of current smoking in European countries (20% medical and 40% dental students) and use of other tobacco products higher in eastern Mediterranean (10%-23%) and European countries (7%-13%). 13 In 2011, the Greek GHPSS study found the prevalence of current smoking among SHP to be 28.8% among pharmacy students, 46.4% among health visitor students and 3 The extremely high rate of exposure to secondhand smoke at least 1 day per week (96.5% in public places and 41.4% at home) corroborate previous studies from Greece, 11 14 and indicate the urgent need for enforcement of tobacco banning policies in enclosed public places throughout the country. The existence of laws banning smoking in school buildings does not appear to affect the rates of smoking in these buildings, which is reflected through the high rates of exposure to secondhand smoke on the school campus (84.1% in the school cafeteria and 77.4% in school buildings).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Countrywide aggregate data from the GHPSS published in 2018 found the highest prevalence of current smoking in European countries (20% medical and 40% dental students) and use of other tobacco products higher in eastern Mediterranean (10%-23%) and European countries (7%-13%). 13 In 2011, the Greek GHPSS study found the prevalence of current smoking among SHP to be 28.8% among pharmacy students, 46.4% among health visitor students and 3 The extremely high rate of exposure to secondhand smoke at least 1 day per week (96.5% in public places and 41.4% at home) corroborate previous studies from Greece, 11 14 and indicate the urgent need for enforcement of tobacco banning policies in enclosed public places throughout the country. The existence of laws banning smoking in school buildings does not appear to affect the rates of smoking in these buildings, which is reflected through the high rates of exposure to secondhand smoke on the school campus (84.1% in the school cafeteria and 77.4% in school buildings).…”
Section: Discussionmentioning
confidence: 99%
“…However, other SHPs such as veterinarians, paramedics, biochemists and others may also play a role in tobacco use cessation. 13 The main objectives of this study were to assess the prevalence of current smoking and secondhand smoke among various groups of SHPs in Central Greece; to identify independent risk factors of current smoking; and to compare knowledge on tobacco cessation methods among different schools of health professions.…”
Section: Open Accessmentioning
confidence: 99%
“…In this regard, our findings are compatible with the results of the study conducted by Meysamie et al 21 . Meanwhile, it is common to observe such a difference between male and female students in other countries as well 22,23 . Focusing on dental students, the status of current cigarette smoking seems much more alarming at SBUMS (52.0%) compared to the status reported at the national level (10.8%) by Keshavarz et al 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Several countries have already applied this survey, pointing out that more than 80% of health students find that health professionals have a role in counseling patients about smoking cessation. However, less than 40% of students reported having received any formal training on tobacco cessation approaches and smoking counseling during their professional education [9]. Recently, we evidenced that 95.5% of dental students mentioned having knowledge about the harmful effects of tobacco during their training.…”
mentioning
confidence: 93%